Micropropagation of Two Economically Important Bamboos : Drepanostachyum falcatum (NEES) Keng and Bambusa balcooa Roxb. - Arya, Sarita; Kant, Abhinav; Sharma, Deepa; Arya, I. D. (Indian Forester, 2008)
A protocol for the micropropagation of two economically important bamboos, Drepanostachyum falcatum and Bambusa balcooa, which have some problems in their conventional propagation, was developed. Nodal explants with single axillary buds were excised from mother plant and were washed with cetavelon. Initially high incidence of fungal contamination was observed in most cultures of Bambusa balcooa, which was controlled by using Bavistin (1%) for 5-7 minutes followed by surface sterilization for 8 -12 minutes with 0.1% HgCl2. Liquid MS medium supplemented with 5.0 mg/l 6-Benzyl Amino Purine (BAP) for Drepanostachyum falcatum and 3.0-5.0 mg/l BAP for Bambusa balcooa was found to be the best for axillary bud induction. The multiple shoots were excised from mother explant and further multiplied on MS medium supplemented with defined plant growth regulators. Best shoot multiplication was observed on MS medium supplemented with 3.0 mg/l BAP for Drepanostachyum falcatum and 3.0 mg/l BAP with 0.5 mg/l Kinetin for Bambusa balcooa. The morphogenetic potential of the axillary buds was adversely affected by phenolic exudates especially in Bambusa balcooa. This was overcome by transferring the explant to the fresh medium after every 12-15 days or whenever the medium turned brown. While a regular subculture in every 3-4 weeks increased the multiplication rate in Drepanostachyum falcatum. In-vitro shoots were rooted when transferred to MS medium supplemented with auxin (IBA, NAA and IAA). The rooted plantlets of Drepanostachyum falcatum were hardened, acclimatized and successfully transferred to field. However the experiments pertaining to optimal rooting response and hardening of Bambusa balcooa are in progress.